COMPARATIVE STUDY ON THE RELATION BETWEEN PHYSICAL AND PSYCHIC HEALTH STATE AND STUDENTS’ SCHOLAR SUCCESS: PRELIMINARY FINDINGS FROM GOTTINGEN AND BACĂU SAMPLES (GYMNASIUM, 2009)
In this study, we used data collected from students of two European academic campuses - Gottingen(Germany) and Bacău (Romania) to examine and compare problems concerning their health status andscholar success. We compared students’ self-reported emotional-behavioural problems and their physical andpsychic status with their ability to be successful in university across the two samples.Consistent with previous research, we found that German students reported more internalizing andexternalizing problems than their Romanians peers did.The identification of similarities, differences, but also the specific aspects of the health statusbetween German and Romanian students was made mostly regarding the risk factors on health. In this study,the socio-cultural particularities constitute the independent variable which can influence the physical andpsychic health. The findings are discussed in relation to an intricate model that shape patterns of academicinvestment.